2009
DOI: 10.3109/17453670903278241
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bone marrow aspiration strategy on the yield and quality of human mesenchymal stem cells

Abstract: Introduction Large inter-donor differences exist in human mesenchymal stem cell (hMSC) yield and the response of these cells to osteogenic stimuli. The source of these differences may be clinical differences in stem cell characteristics between individuals or the aspiration procedure itself.Methods From a total of 23 donors, we aimed to take 2 consecutive 10-mL aspirates from the same site in 17 donors and in 6 donors we aimed to take a 5-mL and a 20-mL aspirate. The aspiration was stopped either when the syri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 11 publications
2
42
1
Order By: Relevance
“…Thus, a single BMA sample of 30-60 ml may not result in an optimal number of MSCs for therapeutic use. Fennema et al [73] suggested aspiration of ≥8 ml to reduce the chance of obtaining a BMA with low cell counts, without affecting the biologic characteristics of the MSCs. Generally, following centrifugation, 2-6 ml of BMACS is prepared for administration.…”
Section: Bone Marrow Biopsy/aspirationmentioning
confidence: 99%
“…Thus, a single BMA sample of 30-60 ml may not result in an optimal number of MSCs for therapeutic use. Fennema et al [73] suggested aspiration of ≥8 ml to reduce the chance of obtaining a BMA with low cell counts, without affecting the biologic characteristics of the MSCs. Generally, following centrifugation, 2-6 ml of BMACS is prepared for administration.…”
Section: Bone Marrow Biopsy/aspirationmentioning
confidence: 99%
“…Each has their own distinct advantages and foibles. Bone marrow has a higher risk to the donor that increases with age, requiring multiple aspirations from multiple sites to obtain optimal numbers 19 and can be painful. Peripheral blood is comparably more convenient for the donor as apheresis avoids anaesthesia and theatre.…”
Section: Sources Of Variationmentioning
confidence: 99%
“…Fennema recommends to harvest at least 8 ml portions, as in lower volume the yield of nuclear cells and MSCs in unpredictable. Also, second portion of up to 10 ml may be taken from the same site without significant loss of quality due to dilution by peripheral blood (Fennema et al, 2009). On the other hand, in older work Muschler concludes that aspiration of more than 2 ml of bone blood results in smaller number of colony forming units -fibroblast (CFU-F) (Muschler et al, 1997).…”
Section: Bone Marrowmentioning
confidence: 99%